1998
DOI: 10.1016/s0042-6989(97)00454-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of luminance on color perception of protanopes

Abstract: Small-field color-naming performance of two protanopes over a 4-log luminance range was impoverished in comparison with that of normal trichromats, and was more strongly affected by changes in luminance. At 200 cd/m2 responses to mid-spectral lights were dominated by 'yellow'; with lowering luminance, 'green' and 'red' were increasingly used. In the color spaces derived from these data the first two dimensions for trichromats are red-green and yellow-blue: those of the protanopes appear to be brightness and 'r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 12 publications
4
27
0
2
Order By: Relevance
“…Further, the experiment revealed that the ability to distinguish colors was more influenced by variation of visual angles for the CVD compared to the normal observers. This corresponds to earlier results by Paramai et al [32] regarding color size effect and visual field, indicating that differences between CVD and normal observers are not significant when larger fields of view (≥3°).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Further, the experiment revealed that the ability to distinguish colors was more influenced by variation of visual angles for the CVD compared to the normal observers. This corresponds to earlier results by Paramai et al [32] regarding color size effect and visual field, indicating that differences between CVD and normal observers are not significant when larger fields of view (≥3°).…”
Section: Discussionsupporting
confidence: 92%
“…Exploring the color size effect for CVD observers, like the work of Pokorny and Smith [30], Nagy et al [31] and Paramai et al [32] indicate a correlation between stimulus size and performance in color-naming tasks as many dichromats show trichromacy in color matching and name the colors in fair agreement with the normal observers in larger fields of view (≥3°). Also, the experiments [31] revealed large individual difference between the observers and that for some observers the ability to discriminate varied considerably as a function of the stimulus parameters, such as field size, luminance level and method of presentation.…”
Section: Color Size Effect and Visual Anglementioning
confidence: 97%
“…It is well established that dichromats often identify colors correctly (some of the time) that are on the same dichromatic line of confusion and that their use of color names does not correspond to their color discrimination ability. [13][14][15][16][17][18][19][20][21] Their use of color names depends on experience, 14,21 size of the stimuli, 15,17,20 both relative and absolute brightness differences in the stimuli, 13,14,16,18,21 and whether there are constraints placed on the color names. 14,19,20 Some of these factors are likely responsible for the error asymmetries in our results.…”
Section: Discussionmentioning
confidence: 99%
“…Nos últimos 25 anos, muitos trabalhos se dedicaram à reconstrução de espaços de cores de indivíduos normais e de indivíduos com defi ciências congênitas (Bimler, 1999;Bimler & Kirkland, 2002;Bimler, Kirkland, & Jacobs, 2000;Bimler & Paramei, 2004;Paramei et al, 1991;Paramei, 1996;Paramei, Bimler, & Cavonius, 1998;Paramei & Bimler, 2001a, 2001bParamei, Bimler, & Cavonius, 2001). Muitos desses trabalhos propuseram a visualização do espaço defi citário como uma deformação do espaço normal.…”
Section: A Reconstrução Dos Espaços De Coresunclassified